A genome-wide cross-cancer meta-analysis highlights the shared genetic links of five solid cancers - Guo, Hongping; Cao, Wenhao; Zhu, Yiran; Li, Tong; Hu, Boheng (Frontiers in Microbiology, 2023)
Breast, ovarian, prostate, lung and head/neck cancer are five solid cancers with complex interrelationships. However, the shared genetic factors of the five cancers were often revealed either by the combination of individual genome-wide association study (GWAS) approach, or by the fixed-effect model based meta-analysis approach with practically impossible assumption. Here we presented a random-effect model based cross-cancer meta-analysis framework for identifying the genetic variants jointly influencing the five solid cancers. A comprehensive genetic correlation analysis (genome-wide, partitioned and local) approach was performed by using GWAS summary statistics of the five cancers, and we observed three cancer pairs with significant genetic correlation, breast-ovarian cancer (r_g=0.221, p=0.0003), breast-lung cancer (r_g=0.234, p=7.6×〖10〗^(-6)), and lung-head/neck cancer (r_g=0.652, p=0.010). Furthermore, random-effect model based cross-trait meta-analysis was conducted for each significant cancer pair, and we found 27 shared genetic loci between breast and ovarian cancer, 18 loci between breast and lung cancer, and 3 loci between lung and head/neck cancer. Functional analysis indicates that the shared genes are enriched in Human T-cell leukemia virus 1 infection (HTLV-1) and Antigen processing and presentation (APP) pathways. Our study investigates the shared genetic links across five solid cancers and will help to reveal the potential molecular mechanisms of them.